Leveraging on cultural and creative industries to foster social innovation: A bibliometric analysis - Giusy Sica; Maria Palazzo; Alessandra Micozzi; Maria Antonella Ferri (Journal of Innovation & Knowledge (JIK), 2025)
This study investigated the interplay between community-based cultural initiatives conducted by Cultural and Creative Industries (CCIs) and social innovation. Selecting peer-reviewed open-access articles that focus on the intersection of culture and innovation was the first step in our systematic literature review. Our analysis focused on the 76 most cited papers that included the keywords 'community-led local development', 'social innovation', and 'cultural and creative industries'. The literature review revealed that CCIs can significantly promote social innovation through cultural engagement, particularly when they collaborate with various stakeholders. However, researchers differ in their emphasis on the nature of collaboration. Some argue that partnerships with businesses or academic institutions are essential for creating 'heterogeneous sources of knowledge' (HSK). Others contend that collaboration between government entities and local authorities is vital for fostering regional and local development. The third perspective introduces the notion of 'entrepreneurial co-creation', suggesting that CCIs work alongside stakeholders with technical and managerial expertise. Finally, there is a consensus that CCIs need to acquire new leadership skills and competencies to ensure sustainability and resilience. By synthesising these four perspectives, this study offers a comprehensive framework that positions CCIs at the core of a broader economic, territorial, managerial, and political context.
Keywords: O35; A14; A12; O01; 650; Social innovation; Culture; Cultural and creative industries; Participation; People-led